Peran Tpq Wijaya Kusuma Dalam Pembinaan Akhlak Anak Di Kampung Srambatan Kota Surakarta - Novenna Citrasari Muria Wijaya; Sukari (4, 2024)
The development of a child's morals cannot be separated from the role of education, both formal education at school and non-formal. Al-Quran Education Park (TPQ) is one of the non-formal educational institutions for children that helps children understand and practice Islamic teachings, including aqidah, worship, and morals. As a non-formal institution that has a role, TPQ certainly requires good management and human resources. As a non-formal institution that has an important role in the education process, in addition there are still many parents who have not been able to educate their children comprehensively with many limitations such as time, knowledge, teaching methods and others. TPQ is expected to take a role in the process of developing children's potential in forming attitudes, knowledge and also skills about religion by using an approach that can adapt to the child's development process based on the Qur'an and AsSunnah. TPQ Wijaya Kusuma in Kampung Srambatan, Surakarta City is a TPQ that is in an environment that is not conducive and risky (High Risk) for children's moral growth. The purpose of this study is to describe the role of TPQ in the formation of children's morals. This study uses a comparative approach with a qualitative type. Data collection techniques are carried out by direct observation to the target TPQ and also open interviews with several research subjects. The results of the study obtained are that there are similarities in both TPQs, namely the personal approach method, giving advice, exemplary behavior and also behavioral habits. While the difference lies in the provision of rewards and punishments in the learning process. Abstrak Pembinaan akhlak seorang anak tidak terlepas dari peran pendidikan, baik pendidikan formal disekolah maupun non formal. Taman Pendidikan Al-qur’an (TPQ) merupakan salah satu wadah pendidikan non formal bagi anak yang membantu anak dalam memahami dan mengamalkan ajaran agama islam, diantaranya aqidah, ibadah, akhlak. Sebagai lembaga non formal yang memiliki peran, TPQ tentu memerlukan manajamen dan sumber daya manusia yang baik. Sebagai lembaga non formal yang memiliki peran penting dalam proses pendidikan, selain itu masih banyak orang tua yang belum mampu mendidik anak secara menyeluruh dengan banyaknya keterbatasan seperti waktu, ilmu pengetahuan, metode mengajar dan lainnya. TPQ diharapkan mengambil peran dalam proses pengembangan potensi anak dalam pembentukan sikap, pengetahuan dan juga keterampilan tentang keagamaan dengan menggunakan pendekatan yang bisa menyesuaikan dengan proses perkembangan anak berlandaskan Al-Qur’an dan AsSunnah. TPQ Wijaya Kusuma di Kampung Srambatan Kota Surakarta adalah TPQ yang berada di lingkungan yang tidak kondusif dan risti (Resiko Tinggi) untuk pertumbuhan ahlak anak. Tujuan penelitian ini untuk mendeskripsikan peran TPQ terhadap pembentukan akhlakul karimah anak. Penelitian ini menggunakan pendekatan komparatif dengan jenis kualitatif. Teknik pengumpulan data dilakukan dengan observasi langsung ke TPQ sasaran dan juga wawancara terbuka terhadap beberapa subjek penelitian. Hasil penelitian yang didapat ialah terdapat kesamaan pada kedua TPQ yaitu metode pendekatan personal, pemberian nasihat, keteladanan dan juga pembiasaan perilaku. Sedangkan perbedaanya terdapat pada pemberian hadiah dan hukuman dalam proses pembelajaran.